Network utilisation and security monitoring using SNMP - Ling, Wei Joon (2020)
A monitor system is important in the filed which consists of network devices and connectivity between them. In this study, we will learn about different type and comparison between monitoring techniques. The challenges in keeping our system free of failure are difficult. A system which cannot be guaranteed to be up during the wholetime operations will make the user frustrated. Besides, system performance and usage also another point where user always concerned with. When the usage on the network or devices if fully occupied, the performance is degraded and eventually cause the services to become unavailable. In this paper, the SNMP protocol is taken into consideration and implementation for network monitoring. The protocol is worked by sending out a message from a central point called management base station to the network devices and those devices return the data information requested back. Throughout the process, the targeted network is closely monitored with SNMP monitoring system and penetration testing will be prosecuted. The outcome produced from the SNMP system is being observed and determine the capability of detecting an attack.